Vitalitas Bahasa Akit di Desa Hutan Panjang, Pulau Rupat, Kabupaten Bengkalis: The Vitality of Akit Language in Hutan Panjang Village, Rupat Island, Bengkalis Regency - Saleh, R; A, Fatmahwati; Arpina, Arpina (Kibas Cenderawasih, 2022)
Local languages preservation could be afforded by means of conservation or revitalization. To determine whether a language can be conserved or revitalized, its vitality status must be known first. The vitality status of Akit language in Hutan Panjang Village, Rupat Island, Bengkalis Regency is still unknown. Therefore, the research focus is to identify the vitality status of Akit language in Hutan Panjang village. The data were collected from the questionnaires spread to the community of Akit tribe in Hutan Panjang village by means of purposive sampling technique. Other than using the questionnaires, the data were also collected by direct observation of the language situation in Hutan Panjang village. The data were analyzed by using quantitative approach namely scoring respondents’ answers, calculating mean score of each question, calculating cumulative index of each indicator, and calculating total index of its vitality. The research shows that the indicator cumulative index of the number of speakers is 0,74, the language contact is 0,72, the bilinguality is 0,86, the dominating position of the speaker community is 0,74, the language use domain is 0,18, the language attitude is 0,72, the regulation is 0,39, the learning is 0,39, the documentation is 0,44, the new challenge is 0,13. The total index score of Akit Language in Hutan Panjang village which is 0,53 is categorized as “deteriorating”. The research recommends the government of Bengkalis regency and Riau Province to afford the preservation of Akit language whether it is in Hutan Panjang or other villages to prevent decreasing status of Akit language.